5-Aminoisoquinolinone reduces renal injury and dysfunction caused by experimental ischemia/reperfusion - Chatterjee, PK (2015)
Background. Poly (ADP-ribose) polymerase (PARP), a nuclear enzyme activated by strand breaks in DNA, plays an important role in the development of ischemia/reperfusion (I/R) injury. The aim of this study was to investigate the effects of a water-soluble and potent PARP inhibitor, 5-aminoisoquinolinone (5-AIQ), on the renal injury and dysfunction caused by oxidative stress of the rat kidney in vitro and in vivo. Methods. Primary cultures of rat renal proximal tubular cells, subjected to oxidative stress caused by hydrogen peroxide (H2O2), were incubated with increasing concentrations of 5-AIQ (0.01 to 1 mmol/L) after which PARP activation, cellular injury, and cell death were measured. In in vivo experiments, anesthetized male Wistar rats were subjected to renal bilateral ischemia (45 minutes) followed by reperfusion (6 hours) in the absence or presence of 5-AIQ (0.3 mg/kg) after which renal dysfunction, injury and PARP activation were assessed. Results. Incubation of proximal tubular cells with H2O2 caused a substantial increase in PARP activity, cellular injury, and cell death, which were all significantly reduced in a concentration-dependent by 5-AIQ [inhibitory concentration 50 (IC50) similar to 0.03 mmol/L]. In vivo, renal I/R resulted in renal dysfunction, injury, and PARP activation, primarily in the proximal tubules of the kidney. Administration of 5-AIQ significantly reduced the biochemical and histologic signs of renal dysfunction and injury and markedly reduced PARP activation caused by I/R. Conclusion. This study demonstrates that 5-AIQ is a potent, water soluble inhibitor of PARP activity, which can significantly reduce (1) cellular injury and death caused to primary cultures of rat proximal tubular cells by oxidative stress in vitro, and (2) renal injury and dysfunction caused by I/R of the kidney of the rat in vivo.